2008
DOI: 10.1124/jpet.107.133868
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin Gene-Related Peptide8-37 Antagonizes Capsaicin-Induced Vasodilation in the Skin: Evaluation of a Human in Vivo Pharmacodynamic Model

Abstract: The purpose of this study was to identify the mediators involved in capsaicin-induced vasodilation in the human skin and to evaluate a pharmacodynamic model for the early clinical evaluation of calcitonin gene-related peptide (CGRP) receptor antagonists. Dermal blood flow (DBF) response of the forearm skin to topically applied capsaicin was measured using laser Doppler perfusion imaging in 22 subjects. The effect of intraarterially administered CGRP 8-37 (1200 ng ⅐ min

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 38 publications
(52 reference statements)
2
39
2
Order By: Relevance
“…The small molecules previously tested in this assay (MK-3207 and telcagepant) displayed higher affinity to CGRP-R than CGRP 8-37 , but still did not block the DBF response completely (Sinclair et al, 2010;Li et al, 2014). Mediators, such as nitric oxide, substance P, and prostaglandins, were previously excluded from playing a significant role in the capsaicin assay (Van der Schueren et al, 2008). Therefore, it might be that a small residual part of the DBF response is mediated by Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The small molecules previously tested in this assay (MK-3207 and telcagepant) displayed higher affinity to CGRP-R than CGRP 8-37 , but still did not block the DBF response completely (Sinclair et al, 2010;Li et al, 2014). Mediators, such as nitric oxide, substance P, and prostaglandins, were previously excluded from playing a significant role in the capsaicin assay (Van der Schueren et al, 2008). Therefore, it might be that a small residual part of the DBF response is mediated by Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In this PD model, the topical application of capsaicin on the skin activates transient receptor potential vanilloid type 1 receptors on Ad-and C-fiber nociceptors (Caterina et al, 1997), which results in the local release of vasoactive substances, including CGRP. The capsaicin-induced DBF change can be quantified using laser Doppler imaging (LDI), and CGRP was identified as the key mediator involved in this model (Van der Schueren et al, 2008). This neurogenic inflammation model, therefore, can be used to evaluate the target engagement of compounds that inhibit the CGRP pathway both preclinically (Salvatore et al, 2008;Benschop et al, 2014) and in clinical development (Salvatore et al, 2010;Sinclair et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, bioactive CGRP fragments may have suppressed sweating. NEP cleaves CGRP into fragments (11), which act differently on nicotinergic ACh receptors (nAChRs): CGRP and CGRP [1][2][3][4][5][6][7] inhibit neuronal nAChRs (20), whereas the shorter fragments CGRP [1][2][3][4][5][6] , CGRP [1][2][3][4][5] and CGRP [1][2][3][4] potentiate the actions of nicotine (21,22). Thus, depending on which fragments prevail, different effects on sudomotor nerve fibres might be expected.…”
Section: Resultsmentioning
confidence: 99%
“…CGRP is important for arteriolar vasodilatation, inducing a long lasting flare reaction, whereas SP causes plasma protein extravasation (oedema), but only short lasting vasodilatation (3)(4)(5). The nociceptive axon reflex flare -a localized increase in superficial blood flow induced electrically or chemically, for example, by acetylcholine (ACh) -can be blocked with CGRP antagonists, but not SP antagonists (2,6,7). Previous experiments showed that CGRP enhances sweating (8), whereas SP might reduce it (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…afferent neurons that will be activated by stimulation of specialized free nerve endings due to damage or intense mechanical, thermal or chemical stimuli [24,25]. The reactive hyperaemia and specific neurogenic effects generated hereby are used to treat rheumatic and neuropathic pain [26]. These effects can be divided into medium- and long-term effects.…”
Section: Introductionmentioning
confidence: 99%